2020
DOI: 10.1111/pbr.12830
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic treatment of microspore‐derived embryos of turnip rape (Brassica rapa) to increase oleic acid content

Abstract: The article presents the results of a study on obtaining mutant doubled haploids of turnip rape. The culture medium for producing embryos in isolated microspore culture was optimized. The optimal medium formula was NLN + 13% S + 0.05 mg/L NAA + 0.05 mg/L BA. Embryos derived from isolated microspore culture were treated with EMS mutagen in three concentrations (4 mM, 8 mM, and 12 mM). Mutant doubled haploid plants and their seeds were obtained. Agronomic evaluation and analysis of fatty acid composition in muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Recently, Kitashiba et al (2016) have identified loci associated with embryo yield in microspore culture of Brassica rapa. Daurova et al changed microspore-derived embryos (MDE) fatty acid composition (Daurova et al, 2020). Genes associated with the induction and the establishment of embryogenesis in isolated microspores were studied by Malik et al (2007), and Tsuwamoto et al (2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kitashiba et al (2016) have identified loci associated with embryo yield in microspore culture of Brassica rapa. Daurova et al changed microspore-derived embryos (MDE) fatty acid composition (Daurova et al, 2020). Genes associated with the induction and the establishment of embryogenesis in isolated microspores were studied by Malik et al (2007), and Tsuwamoto et al (2007).…”
Section: Introductionmentioning
confidence: 99%